2011 6th International Conference on Industrial and Information Systems 2011
DOI: 10.1109/iciinfs.2011.6038056
|View full text |Cite
|
Sign up to set email alerts
|

Tile optimization for area in FPGA based hardware acceleration of peptide identification

Abstract: Abstract-Advances in life sciences over the last few decades have lead to the generation of a huge amount of biological data. Computing research has become a vital part in driving biological discovery where analysis and categorization of biological data are involved. String matching algorithms can be applied for protein/gene sequence matching and with the phenomenal increase in the size of string databases to be analyzed, software implementations of these algorithms seems to have hit a hard limit and hardware … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This identifies clustered peptides (proteins are extracted from mitochondrion of B.P. proteins in UniRef clusters and each peptide extracted is mapped to a particular protein in the UniRef clusters) into categorized automata (several automata are used here representing a maximum of 32 peptides in one automaton that is selected to the optimisation algorithm we developed earlier [21]). In the software implementation we have used Multifast library [17] and modified it for developing our pattern specific automata.…”
Section: Methodsmentioning
confidence: 99%
“…This identifies clustered peptides (proteins are extracted from mitochondrion of B.P. proteins in UniRef clusters and each peptide extracted is mapped to a particular protein in the UniRef clusters) into categorized automata (several automata are used here representing a maximum of 32 peptides in one automaton that is selected to the optimisation algorithm we developed earlier [21]). In the software implementation we have used Multifast library [17] and modified it for developing our pattern specific automata.…”
Section: Methodsmentioning
confidence: 99%
“…For this in-sillico digestion was performed first, with the developed tool allowing mentioned digestion rules. Then the peptides were arranged into a new order and a new categorisation was made according to our optimisation algorithm presented in [13]. Later, protein-peptide mapping was performed offline.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…Studies have been performed considering implementations of Aho-Corasick algorithm on FPGAs as well [6,18]. It is shown that GPUs achieves comparable or higher speedups than CBE-based platforms for computation-intensive applications.…”
Section: Related Workmentioning
confidence: 99%